Relationship of awareness and the Arab Present with Heritage (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Awareness in one of the most important factors for the study of heritage, so as to find the optimal formula of its comprehensive aspects of scientific, philosophical, social, political and economic levels, i.e. the ideological and cognitive levels (philosophical). These two levels have a large role in determining the central point adopted in determining the development of theme of heritage, which forms the most important problems of the current era.